Relationship of serum IgE concentration to level and rate of decline of pulmonary function: the Normative Aging Study. Issue 8 (August 1996) - Shadick, N. A.; Sparrow, D.; O'Connor, G. T.; DeMolles, D.; Weiss, S. T.
Abstract : BACKGROUND: Previous reports on the relationship between serum immunoglobulin E (IgE) concentration and the level and rate of decline of pulmonary function in the general population have produced conflicting results. The relationship between total serum IgE concentration and pulmonary function was therefore examined in 1078 men aged 41-86 years followed in the Normative Aging Study. METHODS: The serum IgE concentration determined at the start of the three year follow up period was examined in relation to both the level and longitudinal rate of decline of forced expiratory volume in one second (FEV1), forced vital capacity (FVC), and FEV1/FVC. RESULTS: In a cross sectional analysis restricted to subjects who had ever smoked cigarettes, multiple linear regression models indicated an inverse association between total serum IgE concentration and both FEV1 (beta = -0.090 1/log10 IU/ml; SE = 0.030; p < 0.005) and FVC (beta = -0.110 1/log10 IU/ml; SE = 0.034; p < 0.005) but not FEV1/FVC, after adjustment for age and height. This relationship persisted when individuals with diagnosed asthma or methacholine hyperresponsiveness were excluded. In subjects who had never smoked cigarettes the total serum IgE concentration was unrelated to spirometric indices. No association was observed in smokers or non-smokers between the serum IgE concentration measured at the beginning of the period of follow up and the decline in FEV1, FVC, or FEV1/FVC. CONCLUSION: Increased levels of serum IgE measured at the beginning of the follow up period are associated with lower levels of pulmonary function but are not predictive of an accelerated rate in the decline of pulmonary function among middle aged and older men.